Implementasi Kegiatan Menggambar Dekoratif Dalam Mengembangkan Kreativitas AUD - Ulya Ainur Rofi'ah; Dewi Safitri; Nur Khotimah (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This research discusses the implementation of decorative drawing activities in the context of developing AUD creativity. Creativity is an important aspect of children's development, and visual arts, especially drawing, has been recognized as an effective means of stimulating their creativity. This study uses the literature study method to collect and analyze various sources of related information. The results of the analysis show that decorative drawing activities make a significant contribution in improving children's abilities in creative thinking, developing fine motor skills, increasing self-confidence, and expanding their social and emotional abilities through interaction in groups. Practical implications of this research include further integration of visual arts activities in AUD education curricula, adequate training for educators, collaboration with parents, and continued research to deepen understanding of the benefits of arts activities in child development. Thus, this research provides a strong foundation for improving AUD education through a holistic approach oriented towards developing children's creativity.